1989
DOI: 10.1063/1.455781
|View full text |Cite
|
Sign up to set email alerts
|

A crossed laser-molecular beam study of the one and two photon dissociation dynamics of ferrocene at 193 and 248 nm

Abstract: A crossed laser-molecular beam study of the one and two photon dissociation mechanism of bis (cyclopentadienyl) iron (ferrocene, FeCp2) has been performed at 193 and 248 nm. By combining electron bombardment mass spectroscopy with time-of-flight (TOF) measurements, the photodissociation mechanism at 193 nm is shown to have two distinct mechanisms. (1) FeCp2+hν→FeCp*+Cp; (2) FeCp+2hν→FeCp+Cp, FeCp→Fe+Cp. For the first mechanism, which accounts for less than 5% of the photodissociation events, the FeCp* velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…In a series of multiphoton dissociation (MPD)/multiphoton ionization (MPI) studies of ferrocene with nanosecond (ns) laser pulses at different wavelengths in the visible and near UV (UV/VIS) it has been shown that the cyclopentadienyl (cp) ligands are lost prior to ionization, and as a consequence, no intact ferrocene cations can be observed in the mass spectra. In the intensive laser radiation field the central iron atom loses its cp rings in one or more MP steps, and the uncaged iron atom can be ionized and detected by a MPI process when the laser wavelength is close to an atomic resonance.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of multiphoton dissociation (MPD)/multiphoton ionization (MPI) studies of ferrocene with nanosecond (ns) laser pulses at different wavelengths in the visible and near UV (UV/VIS) it has been shown that the cyclopentadienyl (cp) ligands are lost prior to ionization, and as a consequence, no intact ferrocene cations can be observed in the mass spectra. In the intensive laser radiation field the central iron atom loses its cp rings in one or more MP steps, and the uncaged iron atom can be ionized and detected by a MPI process when the laser wavelength is close to an atomic resonance.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27] The wavelength dependence of the total ion current spectrum for ferrocene and cobaltocene in the ranges 366-370, 380-390, and 445-455 nm and for nickelocene in the range 375-520 nm was reported. 20,24,25 The features in the excitation spectrum were attributed solely to the metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that the dissociation energy of a second hydrogen atom is lower than that of the first one [38] and therefore six-membered rings of carbon atoms may be quite easily produced by irradiation of photons of 266 nm wavelength, noting that the possibility of multi-photon absorption increases as the state of benzene approaches its critical point due to the formation of large flexible molecular clusters [38] . The decomposition energy of Fe(cp) 2 into Fe + cp + cp is 6.8 eV [39] , whereas that of Co(cp) 2 into Co + cp + cp is 5.64 eV [40] and therefore the decomposition of ferrocene and cobaltocene into iron, cobalt and cp-rings was induced by two-photon absorption during the laser irradiation. Dissociated iron and cobalt atoms were cooled to form the core particles and the carbon layers covering the core particles were formed by cp-rings and six-membered rings of carbon atoms during the interval between two pulses of laser beams [41] .…”
Section: Resultsmentioning
confidence: 99%